Influence of intellectual capital and managerial ownership on sustainability finance the influence of intellectual capital and managerial ownership on sustainability finance - Siti Kustinah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Intellectual capital(IC) or intellectual capital can be said to be the most important resource and or asset in a company where it contains ideas and knowledge which are important elements. Intellectual capital reporting provides companies to integrate reporting and Firm Sustainability Finance in measuring performance. Researchers are interested in conducting research with the aim of examining the effect of intellectual capital and managerial ownership on the sustainability of finance. The research was conducted on LQ45 companies listed on the IDX in 2018-2020. The results of this study reveal that intellectual capital and managerial ownership have a significant effect on the sustainability of finance simultaneously. Partially, intellectual capital has a significant effect on the sustainability of finance, and managerial ownership have no significant effect on the sustainability of finance. This is because the management's share ownership in the LQ45 company is still in the small category so that the management does not benefit from the earnings of the shares they manage.